2016
DOI: 10.1177/1077546316646239
|View full text |Cite
|
Sign up to set email alerts
|

Vibration analysis of smart piezoelectrically actuated nanobeams subjected to magneto-electrical field in thermal environment

Abstract: In this paper, vibration characteristics of magneto-electro-thermo-elastic functionally graded (METE-FG) nanobeams is investigated in the framework of third order shear deformation theory. Magneto-electro-thermo-elastic properties of FG nanobeam are supposed to vary smoothly and continuously along the thickness based on power-law form. To capture the small size effects, Eringen's nonlocal elasticity theory is adopted. By using the Hamilton's principle, the nonlocal governing equations are derived and then solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…In addition, a nonlocal beam model was presented by Simsek [168] for the size-dependent vibration of CNTs subject to a moving load; the nonlocal dynamic deflection is In addition to the stress nonlocality, surface influences on the vibration of nanoscale beams have been studied based on modified continuum models [75,76,[171][172][173][174][175]; it was concluded that surface effects can account for the stiffness hardening, which cannot be described by the nonlocal elasticity theory. In addition, recently size-dependent continuum models incorporating 19 surface and nonlocal effects have been developed for the vibration of smart nanoscale beams such as piezoelectric and magneto-electro-elastic nanobeams [176][177][178][179][180][181] as well as nonhomogeneous nanoscale beams [144,[182][183][184][185].…”
Section: 3d Size-dependent Vibration Of Nanobeamsmentioning
confidence: 99%
“…In addition, a nonlocal beam model was presented by Simsek [168] for the size-dependent vibration of CNTs subject to a moving load; the nonlocal dynamic deflection is In addition to the stress nonlocality, surface influences on the vibration of nanoscale beams have been studied based on modified continuum models [75,76,[171][172][173][174][175]; it was concluded that surface effects can account for the stiffness hardening, which cannot be described by the nonlocal elasticity theory. In addition, recently size-dependent continuum models incorporating 19 surface and nonlocal effects have been developed for the vibration of smart nanoscale beams such as piezoelectric and magneto-electro-elastic nanobeams [176][177][178][179][180][181] as well as nonhomogeneous nanoscale beams [144,[182][183][184][185].…”
Section: 3d Size-dependent Vibration Of Nanobeamsmentioning
confidence: 99%
“…Now, the governing equations in terms of displacements can be derived via substituting Eqs. (20)(21)(22)(23) in Eqs. (13)(14)(15)(16) as:…”
Section: Nonlocal Governing Equationsmentioning
confidence: 99%
“…Nonlocal elasticity theory proposed by Eringen [16,17] is able to consider a wide range of interaction between atoms. Thus, this theory is a suitable candidate for modeling of nanoscale structures [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. This theory is also extensively applied to investigate mechanical behaviors of FG nanoplates [35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Narendar et al [23] investigated wave propagation of MEE-FG nonlocal rods. Also, Ebrahimi and Barati [24][25][26][27] examined free vibration and stability of METE-FG nanobeams based on third-order beam model. According to the above discussion, to the authors' best knowledge, up to now, no study has been carried out on the continuum formulation of buckling behavior of METE-FG nanoplates under external electric and magnetic potentials as well as various thermal environments.…”
Section: Introductionmentioning
confidence: 99%